Free Radicals, Antioxidants and Diseases 2018
DOI: 10.5772/intechopen.77003
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of S-Nitrosothiols in Ischemia- Reperfusion: Role for Mitochondria and Calcium Channels

Abstract: The most important clinical consequence of coronary disease is acute myocardial infarction caused by an occlusion that limits the irrigation to the heart. Although the gold standard treatment is to restore blood flow, this reperfusion causes inherent damage by increasing the size of the infarcted area primarily through the opening of the mitochondrial permeability transition pore (MPTP). The cardioprotective effect of nitric oxide (NO) has been described to operate through S-nitrosylation of several important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Interestingly, mitochondria-targeted S-nitrosothiol inhibits mitochondrial complex I in ischemic tissue reperfusion, preventing the formation of free radicals, thus protecting the heart against post-myocardial infarction heart failure [ 221 ]. It is now becoming clear that S-nitrosation mechanisms leading to cardioprotection involve the S-nitrosation or transnitrosation of mitochondrial proteins, as previously detailed [ 223 , 224 , 225 ]. However, while previous studies have shown a decreased infarcted area after ischemia and improved heart functionality [ 223 , 224 , 225 ], it remains to be proved whether oral nitrite-induced nitrosation results in clinical protection.…”
Section: Pharmacological Cardiovascular Effects Of Increased S-nitros...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mitochondria-targeted S-nitrosothiol inhibits mitochondrial complex I in ischemic tissue reperfusion, preventing the formation of free radicals, thus protecting the heart against post-myocardial infarction heart failure [ 221 ]. It is now becoming clear that S-nitrosation mechanisms leading to cardioprotection involve the S-nitrosation or transnitrosation of mitochondrial proteins, as previously detailed [ 223 , 224 , 225 ]. However, while previous studies have shown a decreased infarcted area after ischemia and improved heart functionality [ 223 , 224 , 225 ], it remains to be proved whether oral nitrite-induced nitrosation results in clinical protection.…”
Section: Pharmacological Cardiovascular Effects Of Increased S-nitros...mentioning
confidence: 99%
“…It is now becoming clear that S-nitrosation mechanisms leading to cardioprotection involve the S-nitrosation or transnitrosation of mitochondrial proteins, as previously detailed [ 223 , 224 , 225 ]. However, while previous studies have shown a decreased infarcted area after ischemia and improved heart functionality [ 223 , 224 , 225 ], it remains to be proved whether oral nitrite-induced nitrosation results in clinical protection.…”
Section: Pharmacological Cardiovascular Effects Of Increased S-nitros...mentioning
confidence: 99%
“…S-nitrosylated cytochrome c oxidase [ 80 ] and F1F0ATPase [ 81 ] has inhibited activity resulting in diminished oxygen and ATP consumption, respectively. SNO of mitochondrial permeability transition pore (MPTP) blocks its opening and thus prevents mitochondrial dysfunction leading to cardiomyocyte death [ 82 ]. On the other hand, SNO augments parkin [ 83 ] and α-ketoglutarate dehydrogenase [ 71 ] activities resulting in the modulation of mitochondrial degradation and prevention of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In general, S-nitrosothiols have shown to be cardioprotective [ 18 ] and several lines of evidence support this notion [ 19 ]. First, NO donors and small S-nitrosothiols were reported to reduce cardiac damage [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%